Analisis Gaya Kepemimpinan Kepala Sekolah: Studi Kasus di SDIT Kasih Ananda - Yumna Khairunnisa; Andriani Sariwardani; Mutoharoh Mutoharoh (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Leadership style is one of the important factors in determining the direction and success of an organization, including in the context of education. Principals, as leaders in education units, have a strategic role in creating a conducive work climate, building collaboration, and improving the quality of education services. The study purpose to identify the principal's leadership style at SDIT Kasih Ananda and its implications for school organizational dynamics. Materials and methods: The research method used is a qualitative case study with structured observation instruments tested for validity and reliability through source triangulation techniques. Data were collected through direct observation using a standardized checklist and respondent confirmation.. Results: The results showed that the principal applied democratic and situational leadership styles. This style has a positive impact on teacher and staff participation, flexibility in decision-making, and an improved collaborative work climate at school. Conclusions: This study concludes that the principal of SDIT Kasih Ananda applies a democratic and situational leadership style, which has a positive impact on staff participation, decision-making flexibility, and a collaborative work climate.